Reliability and availability of the Internet of Things - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The problem of reliability and availability of the Internet of Things (IoT) from the point of view of the classical approach of reliability assessment using MIL-HDBK 217 is discussed in this paper. With the classical approach of reliability assessment using MIL-HDBK 217, only hardware reliability can be assessed, and the situation with the IoT is more complicated: billions of different things (devices), software programs, and human users are involved (networked). The reliability and availability of the IoT is not only a matter of a failure rate of elements (things), but also protocols, standardization, logistics support and other influences. The relation for the reliability calcuation of an IoT system is proposed.
Keywords: reliability; availability; maintainability; Internet of Things